Upgrading of Performance of Diffusion Absorption Refrigeration System - Öztas, Sinan; Gürü Metin; Sözen, Adnan; Kilinc, Cuma; Gülseven Zafer (Journal of Environmental Science and Engineering Technology, 2019)
This paper deals with the effects of absorbent used on the thermal performance of commercial diffusion absorption refrigeration systems (DARSs). For this purpose, an ammonia solution with added lithium bromide was used in the DARS system instead of a commercial ammonia solution of NH3-H2O (NH4OH) (25% ammonia and 75% water), and all comparison experiments used a fixed amount of refrigerant to experimentally investigate the effects on performance. The system cooling performance was calculated by means of experimental data. The performance of all the solutions prepared was compared to each other. The added lithium bromide increased the amount of water absorbed by the coolant, increasing the amount of refrigerant carried to the generator and condenser. Consequently, the thermal efficiency of the system was increased. By using a 5% solution of lithium bromide with the ammonia solution, the thermal performance increased by up to 12%. It was concluded that lithium bromide has a higher refrigerant absorption capability than water in diffusion absorption refrigeration systems.